2023
DOI: 10.1038/s44172-023-00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal removal from coal fly ash for low carbon footprint cement

Abstract: Development of cementitious materials with low carbon footprint is critical for greenhouse gas mitigation. Coal fly ash (CFA) is an attractive diluent additive in cement due to its widespread availability and ultralow cost, but the heavy metals in CFA could leach out over time. Traditional acid washing processes for heavy metal removal suffer from high chemical consumption and high-volume wastewater streams. Here, we report a rapid and water-free process based on flash Joule heating (FJH) for heavy metals remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…To address this problem, Deng et al reported in Communications Engineering 9 a rapid and water-free process for heavy metal removal from CFAs for low-carbon footprint cement. Flash Joule Heating (FJH), an efficient high-temperature technology 10 , was used.…”
Section: Heavy Metal Removal From Coal Fly Ash For Low Carbon Footpri...mentioning
confidence: 99%
“…To address this problem, Deng et al reported in Communications Engineering 9 a rapid and water-free process for heavy metal removal from CFAs for low-carbon footprint cement. Flash Joule Heating (FJH), an efficient high-temperature technology 10 , was used.…”
Section: Heavy Metal Removal From Coal Fly Ash For Low Carbon Footpri...mentioning
confidence: 99%
“…Flash Joule heating (FJH), as a method exhibiting high-energy efficiency and an ultrafast heating rate, has recently been used in the synthesis of many materials including graphene, transition metal chalcogenides, inorganic nanoparticles, , and various other carbide and inorganic compounds. It has also been widely explored as a method for effective remediation of soil and battery electrodes as well as a method for recycling and upscaling materials. In contrast to conventional chemical heating methods, which use conductive or radiative heating, Joule heating requires an electric current to flow through the sample itself, which, in turn, directly heats the feedstock. Passing this electric current through the reactants involves imposing an electrical potential difference, typically up to several hundred volts, across a reaction vessel that is several centimeters across, leading to average electric fields on the order of 10 3 –10 4 V/m and a current density of 10 5 –10 7 A/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Coal power plants worldwide release millions of tons of coal ash annually and are landfilled. The leaching of toxic trace elements and ash spill events make landfills a significant environmental challenge ( Deng et al, 2023 ). The recovery of REEs from FA has several advantages, which include readily available waste products, not requiring extensive excavation, and having a fine powder nature that makes it ideal for chemical processing ( Taggart et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%